Pulmonale Manifestationen bei Kollagenosen = Pulmonary manifestations in collagen vascular diseases - Vogel, Monika Nadja; Kreuter, Michael; Kauczor, Hans-Ulrich; Heußel, Claus Peter (Der Radiologe, 2016)
Clinical/methodical issuePulmonary complications are frequent in patients with collagen vascular diseases (CVD). Frequent causes are a direct manifestation of the underlying disease, side effects of specific medications and lung infections.Standard radiological methodsThe standard radiological procedure for the work-up of pulmonary pathologies in patients with CVD is multidetector computed tomography (MDCT) with thin-slice high-resolution reconstruction.PerformanceThe accuracy of thin-slice CT for the identification of particular disease patterns is very high. The pattern of usual interstitial pneumonia (UIP) representing the direct pulmonary manifestation of rheumatoid arthritis (RA) can be identified with a sensitivity of 45 % and a specificity of 96 %.AchievementsBoth direct pulmonary manifestations, drug-induced toxicity and certain infections can have a similar appearance in thin-slice MDCT in various forms of CVD. Knowledge of the patterns and causes contributes to the diagnostic certainty.Practical recommendationsAt first diagnosis of a CVD and associated pulmonary symptoms thin-slice MDCT is recommended. Clinical, lung function and imaging follow-up examinations should be performed every 6-12 months depending on the results of the MDCT. In every case the individual CT morphological patterns of pulmonary involvement must be identified. The combination of information on the anamnesis, clinical and imaging results is a prerequisite for an appropriate disease management.